Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1515/botcro-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

The first report on periphytic diatoms on artificial and natural substrate in the karstic spring Bunica, Bosnia and Herzegovina

Abstract: -This study presents investigations of the periphytic diatoms on artifi cial (glass slides) and natural substrates in the karstic, limnocrene spring of Bunica situated in the south of Bosnia and Herzegovina. Investigations were performed in summer 2010. Samples were collected every seven days for eight weeks. Physical and chemical characteristics of water, temperature, oxygen saturation, dissolved oxygen, electric conductivity and nutrients as well as fl ow velocity at sample site, were measured simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Also, A. exiguum, G. parvulum, A. ovalis have been previously reported as thermophiles existing at 40-58°C(Quintela et al, 2013;Covarrubias et al, 2016). Moreover, A. exiguum has been recorded in all samples collected from the limnocrene springs of Bunica that are situated in the south of Bosnia and Herzegovina, and this species has been frequently found in many alkaline hot springs(DeDić et al, 2015).…”
mentioning
confidence: 99%
“…Also, A. exiguum, G. parvulum, A. ovalis have been previously reported as thermophiles existing at 40-58°C(Quintela et al, 2013;Covarrubias et al, 2016). Moreover, A. exiguum has been recorded in all samples collected from the limnocrene springs of Bunica that are situated in the south of Bosnia and Herzegovina, and this species has been frequently found in many alkaline hot springs(DeDić et al, 2015).…”
mentioning
confidence: 99%
“…This karst is formed in Upper Jurassic calcareous rock, where Wojtal (2009) described 307 taxa from Kobylanka stream, while Kawecka (2012) found 414 species in 27 karst streams in the Tatra National Park. The karst springs diatom epilithic assemblages in Bosnia and Herzegovina were studied by Dedić et al (2015). Lai et al (2016) also noted epilithic diatom assemblages in a karst spring of Sardinia (Italy) and confirmed ecological potential of the karst features.…”
Section: Discussionmentioning
confidence: 82%
“…glass) in a marine environment provide an opportunity to monitor the initial development and succession of diatoms in the periphyton (NENADOVIĆ et al, 2015;CAR et al, 2020). In contrast, DEDIĆ et al (2015) investigated artificial and natural substrates in a karstic spring and reported that artificial substrates include fewer diatom taxa. However, this might be related to the differences between marine and freshwater ecosystems, whereas generally marine environments provide a greater diatom biodiversity compared to freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%